Intratracheal budesonide supplementation in addition to surfactant improves pulmonary outcome in surfactant‐depleted newborn piglets12. Issue 2 (9th April 2012) - Yang, Chia‐Feng; Lin, Chih‐Hsueh; Chiou, Shr‐Yun; Yang, Yi‐Chiang; Tsao, Pei‐Chen; Lee, Yu‐Sheng; Soong, Wen‐Jue; Jeng, Mei‐Jy
Abstract Severe respiratory distress syndrome (RDS) is still a major cause of mortality and morbidity in premature infants. The combined use of intratracheal corticosteroid and surfactant in severe RDS, which bypasses the systemic circulation, may not only help recruit the lungs but also alleviates pulmonary inflammation without an increase in systemic adverse effects. Twelve newborn piglets received repeated pulmonary saline lavage to create surfactant‐depleted lungs that mimic neonatal RDS, and then were randomly grouped into a control group (standard intratracheal instillation of surfactant‐Survanta 100 mg/kg); and a budesonide (Bude) group (intratracheal instillation with the mixed suspension of Budesonide 0.25 mg/kg and Survanta 100 mg/kg). Blood samples were examined, and the observation period was 24 hr. The results showed that oxygenation was significantly better in Bude group compared to the control group over time (P = 0.016). The proinflammatory cytokines tumor necrosis factor‐α and interleukin‐1 β showed a reduced trend in the Bude group, but was not significantly different from the control group (P > 0.05). Comparing the histological lung injury scores, the Bude group had a significantly lower score than the control group at both dependent and non‐dependent sites (P < 0.05). In conclusion, in piglets with severe RDS, intratracheal instillation of budesonide in addition to surfactant seems to results in a sustained improvement in pulmonary outcome over 24 hr. Pediatr Pulmonol. 2013; 48:151–159. © 2012 Wiley Periodicals, Inc.